(untitled) (Veterinary Science, 2023)
Congenital insufficiency of the right atrioventricular valve is defined as tricuspid dysplasia. The alteration occurs in septal and mural valve leaflets, in chordae tendineae or in papillary muscles. The malformation causes tricuspid regurgitation and presentation of clinical signs associated with congestive right heart failure. Macroscopic lesions include localized or diffuse nodulation or thickening of valves leaflets, short or elongated chordae tendineae, with incomplete development and partial fusion or union, papillary muscles with abnormal attachment or incomplete separation to the right ventricular wall, or absence of one or more muscles. The aim of this work is to provide information and casuistry for diagnostic purposes of a pathology of low prevalence in companion animals. Between 2011 and 2021, 24 canines with a definitive diagnosis of tricuspid dysplasia were treated. The pathology was more frequent in dogs of small to medium size, Poodle (4), Dachshund (3), French Bulldog (3), Yorkshire terrier (2), Bull terrier (1), Boxer (1) and 10 mongrels, 3 under 12 kg and 7 between 12 and 30 kg in weight, medium to large size. The findings are different, race and size, to those observed by other authors. Nodular thickening associated with short chordae tendineae was the most common valve malformation. Tricuspid dysplasia was associated with half (13 of 24) of the cases with pulmonary stenosis. Other congenital anomalies, interventricular and atrial septal defect, were also related. The precise diagnosis of the congenital abnormality of the tricuspid valve apparatus can only be made by echocardiography. Valve alterations, septal leaflet, characterized by nodulation, thickening and union to the interventricular septum, were the most common. The continuous spectral Doppler exploration allowed determining severity, pressures in the atrial and right ventricular chambers and establishing hemodynamic effects of the process and its implication in the prognosis and treatment of the patient.